Conformational Aβ strains and cross-seeding mechanism in Alzheimer’s disease pathogenesis: In vivo studies in transgenic animal models - Gómez Gutiérrez, Rubén (UMA Editorial, 2022)
Accumulation of amyloid-beta (Aβ) fibrils in the brain is associated with Alzheimer’s disease (AD) pathology. These fibrils exhibit distinct conformations or “strains” as consequence of variations in their molecular structure. Moreover, the amyloid structure of proteins has also been associated to important physiological functions, rising the term of functional amyloids. In bacteria these functional amyloids (BFA) are involved in biofilm formation, hence supporting bacterial adhesion, and antimicrobials and cytotoxic activities. Given the heterogeneity of AD and the increasing evidence that bacteria could be involved in AD, this thesis aimed to analyze the in vivo propagation of two different synthetic Aβ1-40 strains (2F and 3F) and the possibility that BFA cross-seed the in vitro and in vivo aggregation of Aβ. 2F and 3F fibrils were characterized by TEM, protease resistance, in vitro aggregation assays and LCOs and BFA (CsgA, microcin E492 and TasA) cross-seeding with Aβ was investigated by in vitro aggregation. To analyze the in vivo propagation, fibrils from all these proteins were intracerebrally administered in 50 days old Tg2576 mice. Prion-like transmission was assessed 250-days post-administration by immunolabeling and ELISA. Results showed that 2F and 3F fibrils induced the formation of Aβ aggregates with distinct brain tropism and unique structural morphologies, resulting in differential glial responses. The three BFA induced the aggregation of Aβ in vitro. However, only CsgA had the ability to cross-seed the in vivo aggregation of Aβ, with all BFA inducing Aβ aggregation with an incomplete attack rate. In conclusion, the distinct Aβ fibrils induced brain amyloidosis and inflammation in vivo, thus raising the possibility that different amyloid conformers might drive the heterogeneity found in AD patients.
Since BFA had the ability to cross-seed the aggregation of Aβ the gut commensal bacteria dysregulation could be a novel AD pathogenic mechanism and a potential therapeutic target.
Keywords: Universidad de Málaga - Tesis doctorales; Alzheimer, Enfermedad de; Péptidos; Proteinas; Alzheimer's; Amyloid-beta; Strains; Cross-seeding